Overview of Dental Anxiety Level of the 6-9 Year Ages who Will Do the Dental Extraction at RSGMP Hasanuddin University - Syam, Irfan Maulana; Ayu Yuniar, Ainun; Tullah, Muh Firdaus; Wulandari, Ayu (Journal of Vocational Innovation, Achievement and Education, 2025)
Anxiety is something that is often experienced by some patients who are about to undergo dental care procedures. Dental anxiety is an anxiety response that is almost identical to a fear response, both of which have physiological, cognitive, and behavioral components. Dental anxiety itself is an important issue to pay attention to because it can cause stress not only to the patient but also to the dentist when providing treatment. This study aims to depict the level of anxiety with changes in blood pressure and pulse rate in children, as well as a psychological depiction of children undergoing tooth extraction at RSGMP Unhas. Method: The type of anxiety assessment was carried out by filling out the MDAS questionnaire, and the assessment of children's behavior was conducted using the Frankl behavior rating scale. Results: The research results showed that, from a psychological perspective, seven children (64%) had low levels of anxiety, and four children (36%) had high levels of anxiety. Children's behavior shows a definite positive attitude and positivity when undergoing the tooth extraction procedure, and from a physiological standpoint, there is an increase in blood pressure and heart rate when the child is in the dental chair.